The fundamental social right to health: the experience of the National Policy of Integrative and Complementary Practices (Revista do Tribunal Regional Federal da 3ª Região, 2024)
This article aims to understand the quality of life in the fundamental social right to health in Brazil as an empirical element offered by the National Policy of Integrative and Complementary Practices (PNPIC) of the Unified Health System (SUS). The problem is organized in the form of a provocation: how important is a political-legal approach to achieving quality of life as an inseparable part of the fundamental social right to health? This is qualitative, exploratory research, outlined by the bibliographic procedure, using the inductive method. As conclusions to the research, it is demonstrated that integrative and complementary health practices (PICS), already made available by the SUS, are revealed as an initial option and foundation for the conceptualization and implementation of the social right to health as a quality of life, providing a relevant path to protection to the complex health context in Brazil.
Keywords: fundamental law; health; quality of life; public policy